Immunocytochemical evidence of Ni-SOD expression in Trichodesmium - Rodriguez, Irene B.; Lazarte, Ivan Alex P.; Ho, Tung-Yuan (Frontiers in Marine Science, 2025)
Trichodesmium is a unique cyanobacterium that concurrently performs both oxygen-generating photosynthesis and oxygen-sensitive nitrogen fixation in the same cells during the photoperiod. We have previously shown that nickel availability positively influences growth and nitrogen fixation rates of Trichodesmium under intense light conditions. The activity of the nickel-containing superoxide dismutase (Ni-SOD) is a critical component of the cellular mechanism exploited by Trichodesmium to attain the sensitive balance between photosynthesis and nitrogen fixation. Here, we studied the interactive effects of Ni and Fe availability on growth and nitrogen fixation rates of Trichodesmium because these act as metal centers of essential enzymes critical in various biochemical processes. Our results show that Ni availability enhances production of hydrogen by Trichodesmium but intracellular levels may be influenced by activity of a NiFe-uptake hydrogenase. Further, we used immunocytochemistry to demonstrate that Ni-SOD was significantly expressed in Trichodesmium, and that it co-occurred with both the Fe-component of nitrogenase enzyme and the D1 protein of PSII. The concurrence of these enzymes indicates that Ni-SOD aids in maintaining low intracellular levels of reactive oxygen species (ROS) by rapidly converting superoxide released by photosynthetic systems into hydrogen peroxide. Our results showing that Ni-SOD coexists with a photosynthetic protein and the nitrogenase enzyme supports the role of Ni-SOD in the protective mechanism employed by Trichodesmium.